2018
DOI: 10.1186/s40657-018-0124-7
|View full text |Cite
|
Sign up to set email alerts
|

Research advances of Galliformes since 1990 and future prospects

Abstract: Background: Galliformes are widely distributed throughout the world and economically important to humans as domesticated animals or gamebirds. They are at a unique position for advancing knowledge and techniques of wildlife conservation as the barometer of the status of applied ecology. Populations of many galliform species have declined mainly due to habitat loss and over-hunting. An assessment of knowledge of Galliformes could help to provide guidelines for future research and conservation strategies. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 148 publications
0
10
0
Order By: Relevance
“…spruce grouse Falcipennis canadensis (Herzog & Keppie, 1980) and blue grouse Dendragapus obscurus (Cade & Hoffman, 1993). Tian et al (2018) emphasized the lack of research on long-term monitoring and life history information in many Galliformes species in which reduces the success of conservation, here I present the first study to quantify explicitly partial migration in ptarmigan. Partly in line with my first hypothesis, I found that body size (weight) affected the decision to migrate or to remain resident, but this effect was only found among juvenile birds.…”
Section: Discussionmentioning
confidence: 99%
“…spruce grouse Falcipennis canadensis (Herzog & Keppie, 1980) and blue grouse Dendragapus obscurus (Cade & Hoffman, 1993). Tian et al (2018) emphasized the lack of research on long-term monitoring and life history information in many Galliformes species in which reduces the success of conservation, here I present the first study to quantify explicitly partial migration in ptarmigan. Partly in line with my first hypothesis, I found that body size (weight) affected the decision to migrate or to remain resident, but this effect was only found among juvenile birds.…”
Section: Discussionmentioning
confidence: 99%
“…However, demographic data on Vietnam Pheasant are very sparse and, on wild birds, non-existent. Other Lophura pheasants can furnish missing parameter values, but among galliform genera receiving research attention in the past 30 years Lophura has had the least (Tian et al 2018), and in any case the few results can be highly variable-e.g. Siamese Fireback L. diardi occurring at a density of 5.6 birds per km 2 in Thailand (Suwanrat et al 2014) but Kalij Pheasant L. leucomelanos averaging 321 birds per km 2 in Hawai'i (Zeng 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Populations of many galliform species have declined mainly due to habitat loss and over-hunting [ 1 ], including those in captivity [ 2 ]. Notably, the Congo peacock ( Afropavo congensis ), which inhabits the forested areas of the Democratic Republic of the Congo, has been classified as a vulnerable species by the International Union for Conservation of Nature (IUCN) [ 3 ].…”
Section: Introductionmentioning
confidence: 99%